2014
DOI: 10.1504/ijep.2014.065903
|View full text |Cite
|
Sign up to set email alerts
|

Study of the urban heat island in Lecce (Italy) by means of ADMS and ENVI-MET

Abstract: The Urban Heat Island (UHI) phenomenon is associated to a cascade of effects on citizens' health, energy consumptions and air quality. Accurate local scale UHI numerical predictions are particularly relevant for the achievement of a sustainable urban planning. In this paper, we evaluate the performance of two different modelling techniques to predict temperature distribution within the urban environment. The diagnostic integral-semi-Gaussian model ADMS-Temperature and Humidity Model and the prognostic Computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…of the limitations the simulation results may not be accurate enough for absolute quantification, they are sufficiently accurate for studying relative differences. Furthermore, although ENVI-met may not be capable of deriving rigorous quantitative results at a specific time, it can nevertheless accurately depict the trend of changes (Maggiotto et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…of the limitations the simulation results may not be accurate enough for absolute quantification, they are sufficiently accurate for studying relative differences. Furthermore, although ENVI-met may not be capable of deriving rigorous quantitative results at a specific time, it can nevertheless accurately depict the trend of changes (Maggiotto et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ENVI-met was chosen for this investigation because of its ease of use and dependability in measuring urban microclimatic changes such as thermal comfort (PMV) and mean radiation temperature (TMRT). ENVI-met has been rigorously tested for evaluating urban design solutions in outdoor thermal settings [47][48][49][50][51][52]. It outperforms other methods for predicting urban microclimate conditions as the best model for assessing human comfort at street level.…”
Section: Using Envi-met Microclimate Modelmentioning
confidence: 99%
“…As for microclimate, only few studies, both experimental and modeling, were performed. Maggiotto et al [50,51] discussed the performance of the temperature perturbation-type Atmospheric Dispersion Modelling System (ADMS)-Temperature and Humidity Model (ADMS-TH) and ENVI-met for the prediction of urban air temperature using field measurements they collected in the summer of 2012. Direct comparisons with measured data and statistical indices showed that modeled results were within the range of acceptance.…”
Section: A Brief Overview Of Recent Microclimate and Air Quality Studies In Leccementioning
confidence: 99%
“…ENVI-met was successfully employed in studies analyzing the effects of vegetation on microclimate and thermal comfort in the urban environment, where it was thoroughly described [34][35][36][37][38][39][40]; it was also employed for an investigation of air quality, focusing on air pollutant deposition and dispersion in several studies [41][42][43][44][45][46][47][48][49], which mostly found a satisfactory agreement with observations and concluded that, although it is not a very sophisticated model, it provides sufficient functions for establishing small-scale pollutant distribution for studies of urban greening in near-road environments. Specifically, the model was only applied to evaluate the microclimate in some districts of Lecce [50][51][52], while, to our knowledge, there are no papers applying the model to evaluate the impact of urban greening on the dispersion of air pollutants in the city of Lecce.…”
Section: Introductionmentioning
confidence: 99%